PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN WORDWALL TERHADAP KEMAMPUAN BERFIKIR TINGKAT TINGGI PADA PEMBELAJARAN MATEMATIKA - Nuraini Lutfin Nisa; Rida Fironika Kusumadewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of the Problem Based Learning (PBL) model assisted by Wordwall media on students’ higher-order thinking skills and learning outcomes in mathematics, specifically on the topic of perimeter of plane figures. The research was conducted at SD Negeri 3 Brabo involving 20 fifth-grade students, divided into an experimental group and a control group. The study used a true-experimental design with a posttest-only control design. Instruments included higher-order thinking skill tests and mathematics learning outcome tests. Data were analyzed using normality tests, homogeneity tests, and t-tests. The results showed that the experimental group outperformed the control group in both higher-order thinking skills and mathematics learning outcomes. These findings indicate that the implementation of the PBL model with Wordwall media had a significant influence on students' learning performance regarding the perimeter of plane figures.